Interaction Between Toxic and Essential Metals in The Biological System, and Their Effect on Animal Health - Darmono . (Indonesian Center for Animal Research and Development, 1999)
Among the various toxic elements, heavy metals such as Cd, Pb, and Hg are commonly present in the environment. These metals have no biological function in the animal, but their presence in tissues reflect contact of the organism with its environment. Studies of the toxicity mechanism of these elements in the biological systems of the animals are important especially interaction between them and some essential dietari elements like Ca, Zn, Fe, Se, and Cu. In general a deficiency from one of the essential element increases toxicity of heavy metals, whereas an excess appears to be protective. These suggest that dietary presence of the essential elements may to protection of animal from the effects of heavy metal exposure. Addition of essential elements in the diet can be used for the treatment of heavy metal toxicity. Key words : Toxic metals, essential metals, interaction